Radial and axial vibration modes of graphyne nanotubes. (June 2022) - Liu, Fu; Tang, Xiaoting; Du, Wan; Chi, Baoqian; Zhao, Xinluo; Liu, Yi
Abstract: The radial breathing modes (RBM) of carbon nanotubes (CNTs) arise from the collective inward and outward vibration along the radial direction of tubes, becoming characteristic Raman vibrational modes widely used for determining the radii of CNTs. The graphyne nanotubes (GNTs) can form by rolling graphyne sheets in a similar way as the CNT formation from rolled graphene sheets. In this work the atomic configuration and vibration modes of the GNTs with varied chirality and radii were investigated by classical molecular dynamics. The GNTs exhibit RBMs with an inversed linear relationship between the RBM vibration frequencies and radii, similar with those of CNTs. More importantly, we reported an axial vibrational mode (AVM) of the GNTs where the vibration waves propagate along the axial direction of the GNTs. The AVM is a unique vibration mode of GNTs due to the more flexible sp bonded carbon chain atoms arranged along the tube axis, providing additional axial vibration degree of freedom. The features of phase difference of the standing axial waves depend on the structure types of GNTs: The armchair GNTs exhibit zigzag-like sawtooth waves, while the zigzag GNTs have armchair-like square waves. The AVMs of GNTs can be regarded as transverse acoustic phonon modes of carbon atom chains at low frequency ranges. Moreover, the AVMs of GNTs generally have higher frequencies than the RBMs of CNTs with similar diameters. Therefore, our simulation suggests that AVM may be used as a fingerprint vibrational mode of GNTs for the refined structure characterization in experiments. The AVM may also be the origin of low thermal conductivity of GNTs with implications as thermoelectric materials. Graphical Abstract: ga1 Highlights: The graphyne nanotubes (GNTs) exhibit unique axial vibrational modes (AVM) along the axial direction of tubes. The armchair GNTs exhibit zigzag-like sawtooth waves, while the zigzag GNTs have armchair-like square waves. The AVMs of GNTs can be regarded as transverse acoustic phonon modes of carbon atom chains at low frequency ranges. The AVM is a unique vibration mode of GNTs due to the more flexible sp bonded carbon chain atoms along the tube axis. The graphyne nanotubes (GNTs) have radial breathing modes (RBM) similar with those of carbon nanotubes (CNTs).